High-energy diffraction of particles and nuclei - Jenkovszky, László; Nagy, István (Вопросы атомной науки и техники, 2012)
After a brief historical overview, we present recent results on high-energy diffraction, elastic and inelastic, with emphasis and comments on the recent experimental results from the Large Hadron Collider (LHC) at CERN. После краткого исторического введения представлены новые результаты об упругой и неупругой дифракциях с учетом недавних экспериментальных результатов, полученных на Большом Адронном Коллайдере. Після короткого історичного вступу представлено нові результати про пружню та непружню дифракції з врахуванням нещодавніх експериментальних результатів з Великого Адронного Колайдера.